Localization of pancreatic endocrin tumours by endoscopic ultrasonography - Bülent YILDIRIM; Uğur YILMAZ; K. Bahri ATEŞ; Ülkü SARITAŞ; Gülay TEMUÇİN; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-